A 4CIT PROJECT-BASED LEARNING MODEL TO IMPROVE THE STUDENTS SPEAKING SKILLS - Widyawati Palupi (International Conference on Teaching and Learning, 2024)
This study concerns developing 4CIT Project-Based Learning to improve junior high school students’ speaking skills. The objectives are to describe the process of creating the 4CIT project-based learning model, the holistic improvement in the speaking skills of junior high school students, and the strengths and limitations of developing the 4CIT project-based learning model in improving students’ speaking skills. This Design-Based Research consists of analysis of practical problems by researchers and practitioners in collaboration, development of solutions informed by existing design principles and technological innovations, iterative cycles of testing and refinement of solutions in practice, and reflection to produce “design principles” and enhance solution implementation. The model’s components cover the lesson plan and the 4CIT Project-Based Learning Model syntaxes such as coaching, grouping, selecting the topic, designing and consultation, presentation, display, and review and reward. The 4CIT Project-Based Learning Model is not only designed to help English teachers implement a clear and practical model to improve the students’ speaking skills, but also to give opportunities for the students to explore their skills of communication, collaboration, creativity, and critical thinking which relates to information technology to support their speaking practice.